Towards tourists’ perspective: Creative tourism and its main characteristics - Watsida Boonyanmethaporn; Arif Kamisan Pusiran; Yuzainy Janin (NIDA Development Journal, 2024)
The development of creative tourism has seen significant growth; tourists are active co-creators of their own experience and have become increasingly interested in learning about the cultural surroundings of the destinations they visit, through contact with the local people and their culture. Therefore, the integration and development of creative tourism is an inevitable choice for achieving regional economic and cultural appreciation. This paper aims to expound the concept of creative tourism and to determine the creative tourism characteristics from the tourist perspective. Exploratory factor analysis was employed to uncover the various said perspectives which pertain to creative tourism in the context of activity participation. The factors are categorized into five aspects: genuine value, co-creation experience, spirit of place, hands-on experience and cross-cultural experience. Finally, the development of creative tourism characteristics is recommended in developing creative tourism as well as creative tourism-related activities to promote the integration of creative industry and to strengthen the linkage between that of tourism and other industries.